History of Oil Extraction Process in High Viscosity Deposits - Ermatov Navruz Khushmurodovich; Bekjonov Rozisher Soatmurodovich; Orziyev Shohruh Nuriddinovich; Akhatova Guliza Anvarovna (Scientific Trends, 2024)
Oil and gas have been known to humanity for a long time, and the consumption of products obtained from them in the national economy and the need for them have been increasing year by year. Oil has been used in Uzbekistan since ancient times. Due to its characteristic pungent smell, oil has been used in the fight against agricultural pests.
Keywords: Field, product, high oil viscosity, carbonate reservoirs, geologic model, waterflooding, kerosene.